2020
DOI: 10.3390/ijerph17010340
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment Indicators for the Left-Behind Elderly in Rural China: A Delphi Study

Abstract: In China, many young and middle-aged rural residents move to urban areas each year. The rural elderly are left behind. The number of the rural left-behind elderly is increasing with urbanization, but it is unclear which indicators can be used to assess their health condition. The health risk assessment index system was developed to improve the health level of the rural left-behind elderly. A two-round web-based Delphi process was used to organize the recommendations from fifteen Chinese experts in geriatrics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Previous research has shown that EH has distinct patterns across urban and rural settings [62], with the results of our study providing evidence aligned with the literature. In rural settings, water and sanitation dimensions have been shown to have more impact on health [63], and Badland et al [25] showed that air pollution, housing, public open spaces, and transport are the most important aspects in assessing health in urban settings.…”
Section: Eh In Urban Settingssupporting
confidence: 91%
“…Previous research has shown that EH has distinct patterns across urban and rural settings [62], with the results of our study providing evidence aligned with the literature. In rural settings, water and sanitation dimensions have been shown to have more impact on health [63], and Badland et al [25] showed that air pollution, housing, public open spaces, and transport are the most important aspects in assessing health in urban settings.…”
Section: Eh In Urban Settingssupporting
confidence: 91%
“…14 15 Numerous studies have demonstrated that left-behind elderly individuals are at a higher risk of chronic physical illnesses, loneliness, and depressive and anxiety symptoms than non-left-behind elderly individuals. [15][16][17] Because these factors have been linked to an increased risk of cognitive impairment, [18][19][20][21] leftbehind older adults may have poorer cognitive function than those with nearby family members. However, the limited available studies have reported mixed findings, showing positive, negative or non-significant associations between left-behind status and cognitive impairment in older adults.…”
Section: What This Study Addsmentioning
confidence: 99%
“…25–27 While this term generally refers to older adults whose adult children have left their parents’ homes, the criteria for operationalising left-behind status vary widely across studies, such as the number of adult children who have migrated out (ie, any vs all), the duration of out-migration (ie, 6 vs 10 months per year), the distance between older parents’ homes and adult children’s current place of residence (ie, living in different communities vs cities) and the frequency of adult children’s visits to their parents (ie, ≤2 vs ≤4 times per year). 15–17 22 28 29 …”
Section: Introductionmentioning
confidence: 99%
“…The survey's results showed that the depression factor scores for left-behind boys were higher than those for non-left-behind boys, while the depressive symptom factor scores in female children was higher than for male children. The depressive symptom factor scores in only children among left-behind children were higher than for non-only children among left-behind children [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%